Pharmacogenetic Association of the Galanin Receptor (GALR1) SNP rs2717162 with Smoking Cessation - Gold, Allison B (Nature Publishing Group, 2012)
Galanin modulates dopaminergic neurotransmission in the mesolimbic dopamine system, thereby influencing the rewarding effects of nicotine. Variants in the galanin receptor 1 (GALR1) gene have been associated with retrospective craving severity and heaviness of smoking in prior research. We investigated pharmacogenetic associations of the previously studied GALR1 polymorphism, rs2717162, in 1217 smokers of European ancestry who participated in one of three pharmacogenetic smoking cessation clinical trials and were treated with nicotine patch (n=623), nicotine nasal spray (n=189), bupropion (n=213), or placebo (n=192). The primary endpoint was abstinence (7-day point prevalence, biochemically confirmed) at the end of treatment. Cravings to smoke were assessed on the target quit day (TQD). The longitudinal regression model revealed a significant genotype by treatment interaction (P=0.03). There was a reduced odds of quitting success with the presence of at least one minor (C) allele in the bupropion-treated group (OR=0.43; 95% CI=0.22–0.77; P=0.005) but equivalent quit rates by genotype in the nicotine-replacement therapy groups. This genotype by treatment interaction was reproduced in a Cox regression model of time to relapse (P=0.04). In the bupropion trial, smokers carrying the C allele also reported more severe TQD cravings. Further research to identify functional variants in GALR1 and to replicate pharmacogenetic associations is warranted.